What does It Mean to be Ethical in Research? What should It Mean? - Mokhamad Anwar (Jurnal Bisnis Manajemen, 2015)
Research Ethics has become one of the most important issues in research activities. Many professional associations, government agencies, and universities have approved specific codes, rules, and policies relating to research ethics. Nuremberg Code 1947 has been a prominent reference for being adopted by organizations in conducting research ethics.This paper tries to explain what research ethics  means, how important ethics  in  research  activities,  and some  ethics  principles  which many  experts  shed  light on and currently  prevail  in  many organizations including universities. In the end of this paper, it is revealed some of those principles that could be more appropriate to be paid  more  attention  related with the qualitative and quantitative methods employed.